Photothermal Films: Transparent Photothermal Heaters from a Soluble NIR‐Absorbing Diimmonium Salt (Adv. Mater. 1/2020). Issue 1 (7th January 2020) - Han, Minsu; Kim, Byeonggwan; Lim, Hanwhuy; Jang, Hwandong; Kim, Eunkyoung
Abstract : A highly transparent diimmonium (DI) salt selectively absorbs light in the NIR range to provide a transparent photothermal film with a high conversion efficiency, as described by Eunkyoung Kim and co‐workers in article number 1905096 . The film made of DI affords a transparent soft actuator and heater that can generate a transparent hot Venus flytrap device.